How Useful is Inequality of Opportunity as a Policy Construct? - Kanbur, Ravi; Wagstaff, Adam (World Bank Group, Washington, DC, 2014)
The academic literature on equality of opportunity has burgeoned. The concepts and measures have begun to be used by policy institutions, including in specific sectors such as health and education. It is argued that one advantage of focusing on equality of opportunity is that policy makers are more responsive to that discourse than to equality of outcomes per se. This paper presents a critique of equality of opportunity in the policy context. Although the empirical analysis to which the literature has given rise is useful and is to be welcomed, current methods for quantifying and implementing the concept with a view to informing the policy discourse face a series of fundamental questions that remain unanswered. Without a full appreciation of these difficulties, the methods may prove to be misleading in the policy context.